2020
DOI: 10.21037/jtd-20-1914
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of COVID-19 infection in chronic obstructive pulmonary disease: a multicenter, retrospective, observational study

Abstract: Background: Coronavirus disease 2019 (COVID-19) has been a global pandemic disease, with more than 4 million cases and nearly 300,000 deaths. Little is known about COVID-19 in patients with chronic obstructive pulmonary disease (COPD). We aimed to evaluate the influence of preexisting COPD on the progress and outcomes of COVID-19. Methods: This was a multicenter, retrospective, observational study. We enrolled 1,048 patients aged 40 years and above, including 50 patients with COPD and 998 patients without COPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 21 publications
7
62
0
4
Order By: Relevance
“…Extensive studies have suggested that COVID-19 patients with any comorbidity were more likely to develop severe organ injury related to pre-existing diseases. A retrospective cohort study of 3,069 hospitalized patients with COVID-19 in US demonstrated that patients with cardiovascular disease (CVD) were more likely to have myocardial injury than patients without [23]. In addition, patients with pre-existing renal diseases were more susceptible to develop renal complications induced by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have suggested that COVID-19 patients with any comorbidity were more likely to develop severe organ injury related to pre-existing diseases. A retrospective cohort study of 3,069 hospitalized patients with COVID-19 in US demonstrated that patients with cardiovascular disease (CVD) were more likely to have myocardial injury than patients without [23]. In addition, patients with pre-existing renal diseases were more susceptible to develop renal complications induced by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, compared with COVID-19 patients without chronic obstructive pulmonary disease (COPD), patients with COPD were more likely to develop pulmonary bacterial or fungal coinfection (20.0% vs . 5.9%), ARDS (20.0% vs. 7.3%), and septic shock (14.0% vs. 2.3%) [ 23 ]. In addition, patients with pre-existing renal diseases were more susceptible to develop renal complications induced by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal blood purification with continuous renal replacement therapy (CRRT), as the most common technique in clinical practice, played an important role in the rescue of SARS, MERS and other sepsis-associated AKI 92 . Approximately 0.4-2.3% of COVID-19 patients required CRRT, with AKI as the main reason 6 , 12 , 93 . The proportion increased to 5.6-23.0% in critically ill patients in the ICU 2 , 3 , 7 , 10 , 71 .…”
Section: Treatment Of Covid-19-associated Acute Kidney Injurymentioning
confidence: 99%
“…COPD up-regulated ACE-2 expression in lower airways, which in part may explain the increased risk of severe COVID-19 or mortality in patients with COVID-19 and COPD 7 . Previously studies showed a worse outcomes in patients with COVID-19 and COPD compared with those without COPD, while did not descript the risk factors for mortality in these population 8,9 . Additionally, a proportion of COPD infected COVID-19 will treat their illness at home probably under the pandemic of COVID-19 10 .…”
Section: Introductionmentioning
confidence: 85%